The rich pharmacological activities of Magnolia officinalis and secondary effects based on significant intestinal contributions. (5th December 2021) - Niu, Lin; Hou, Yuanyuan; Jiang, Min; Bai, Gang
Abstract: Ethnopharmacological relevance: Magnolia officinalis Cortex ( M. officinalis ) is a traditional herbal drug widely used in Asian countries. Depending on its multiple biological activities, M. officinalis is used to regulate gastrointestinal (GI) motility, relieve cough and asthma, prevent cardiovascular and cerebrovascular diseases, and treat depression and anxiety. Aim of the review: We aimed to review the abundant form of pharmacodynamics activity and potential mechanisms of action of M. officinalis and the characteristics of the internal processes of the main components. The potential mechanisms of local and distance actions of M. officinalis based on GI tract was provided, and it was used to reveal the interconnections between traditional use, phytochemistry, and pharmacology. Materials and methods: Published literatures about M. officinalis and its main components were collected from several scientific databases, including PubMed, Elsevier, ScienceDirect, Google Scholar and Web of Science etc. Results: M. officinalis was shown multiple effects including effects on digestive system, respiratory system, central system, which is consistent with traditional applications, as well as some other activities such as cardiovascular system, anticancer, anti-inflammatory and antioxidant effects and so on. The mechanisms of these activities are abundant. Its chief ingredients such as magnolol and honokiol can be metabolized into active metabolites in vivo, which can increase water solubility and bioavailability and exert pharmacological activity in the whole body. In the GI tract, M. officinalis and its main ingredient can regulate GI hormones and substance metabolism, protect the intestinal barrier and affect the gut microbiota (GM). These actions are effective to improve local discomfort and some distal symptoms such as depression, asthma, or metabolic disorders. Conclusions: Although M. officinalis has rich pharmacological effects, the GI tract makes great contributions to it. The GI tract is not only an important place for absorption and metabolism but also a key site to help M. officinalis exert local and distal efficacy. Pharmacodynamical studies on the efficacies of distal tissues based on the contributions of the GI tract hold great potential for understanding the benefits of M. officinalis and providing new ideas for the treatment of important diseases. Graphical abstract: Magnolia officinalis Cortex has plenty of pharmacological activities and gastrointestinal (GI) tract contributes a lot to it. In addition to rich gastrointestinal activity, Magnolia officinalis can also exert multisystem efficacy through GI absorption and transport or secondary effects based on intestinal effects. Image 1 Highlights: Highlight: The pharmacological activities of M. officinalis were reviewed systematically and their main mechanisms were summarized. Metabolism and pharmacokinetic features of the principal components were summarized. The potential mechanisms of local and distance actions based on gastrointestinal tract were highlighted.